PENGEMBANGAN PARIWISATA DAN PENGENTASAN KEMISKINAN - Kusuma Wulandari; Nur Dyah Gianawati; Franciscus Adi Prasetyo (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2022)
Tourism development is one of the mainstays in village development, especially to reduce poverty. Pro-Poor Tourism (PPT) is a tourism perspective that seeks to bring various benefits to the poor, including social, environmental, and cultural benefits in addition to economic benefits. PPT does not aim to expand the size of the sector, but opens opportunities for the poor in tourism, at all levels and scales. The approach in this research is qualitative-descriptive. Determination of informants was done by using purposive sampling technique. The data processing of this research went through some stages such as reviewing all data, compiling transcripts of interview results, coding data, categorizing data, compiling temporary conclusions, analyzing and compiling final conclusions. This study aims to analyze and discuss the development of community-based tourism and poverty reduction based on the perspective of Pro-Poor Tourism (PPT). The developmentof a tourism village in Glingseran has provided benefits for the village community, namely releasing the title of poor village so that the development of a tourisim village is in accordance with the philosophy of the Pro-Poor Tourism (PPT) perspective which is oriented to providing economic benefits, including creating jobs for rural communities. The culture of the Glingseran people, such as Solawatan and Sedekah Bumi, has come back tolife with village tours.